L‐leucine promotes axonal outgrowth and regeneration via mTOR activation. Issue 5 (4th April 2021) - Ma, Chao; Teng, Long; Lin, Ge; Guo, Beibei; Zhuo, Run; Qian, Xiaowei; Guan, Tuchen; Wu, Ronghua; Liu, Yan; Liu, Mei
Abstract: Discovering safe and effective drugs that promote neuron regeneration is an essential strategy for the recovery of central nervous system injuries. In this study, we found that L‐leucine, an essential amino acid obtained from both supplements and food sources, could dramatically boost axonal outgrowth and regeneration. First, the effects of L‐leucine on neurons were evaluated by cell apoptosis, survival, and death assays, and the results showed no changes in these processes after treatment. By live cell imaging, L‐leucine was found to remarkably increase axonal length and growth velocity after axotomy. We also verified that L‐leucine enhanced p‐mTOR/p‐S6K activation in neurons by testing with an mTOR inhibitor, rapamycin. Thereafter, we investigated the effects of L‐leucine on the spinal cord injury in vivo. A mouse model of spinal cord hemi‐section was established, and L‐leucine was administered by tail intravenous injection. Basso mouse scale values revealed that L‐leucine could improve functional recovery after injury. It was also notable that L‐leucine treatment promoted axon growth across chondroitin sulfate proteoglycan (CSPG) areas. Furthermore, we used CSPGs as inhibitory environmental cues and clarified that L‐leucine significantly enhanced axonal outgrowth and regeneration by promoting p‐mTOR and p‐S6K activation. Therefore, our study is the first to report that L‐leucine promotes axonal regeneration in vitro and in vivo and could be candidate drug for axonal re‐growth and nervous functional recovery.